Charity and Nationalism: The Case of ‘Abd Allah al-Nadim’s Islamic Philanthropic Society - Gamal-Eldin, Mohamed Amr (AUC Knowledge Fountain, 2012)
My paper argues that charity can be used as a lens to examine nationalism. Due to the transformation of the institution of charity in late nineteenth-century Egypt new charities were developed. In the nineteenth century charity was changing due to the state centralization policies of Mehmed ‘Ali (r. 1805-48), who founded state-run shelters and soup kitchens and enacted prohibitions against begging. Later because of decentralization policies under Said Pasha (r.1854-1863) and Khedive Ismail (r.1863-1879), there was a move away from state control of charity, and the gradual erection of a number of private charitable associations that aimed to help the “public” poor. I look at how the evolving nineteenth-century institutions of charity, both changes under Mehmed ‘Ali and later under his successors, differed from the “pre-modern” period. Is nineteenth-century charity similar to early charity, in particular the ‘awqaf (endowments) of Mamluk elites that became a symbol of the rulers’ beneficence? What did donation and beneficence mean in late nineteenth-century Egypt? And did the new charitable associations of the late nineteenth century, that were not an individual endowment (waqf) or state-controlled charity, begin to use their power of beneficence to improve the social conditions of people with the goal to mold a particular type of Egyptian citizen? This connection between charity and the modeling of a better citizen will constitute a central theme of my argument. My research concentrates on one Islamic charity created around the period of the 1881-2 ‘Urabi revolution, which are the years that are considered as the coming of age of the Egyptian nationalist movement. As such, my project’s periodization falls between 1879 and 1892 in order to obtain a detailed picture of charity within the early Egyptian nationalist movement. It focuses on the Islamic Philanthropic Society (IPS), founded in 1879, by ‘Abd Allah al-Nadim. The IPS was a nationalist organization, where both Egyptian territorial nationalism and Islamic nationalism were at work, with a mission to educate young poor Egyptians against what was perceived to be a growing foreign hegemony caused by the British occupation. Specifically, I will study how the IPS evolved, how its charity was donated, how it was received and perceived by its recipients in the late nineteenth century. My work expands on the current literature by looking at the connections between charity and nationalism, rather than looking specifically at the school/education side of the IPS alone. Instead of the individual contributing for themselves, or establishing their own endowment, like the many waqfs created to fund a madrassa or a kuttab, the new charitable associations of the late nineteenth century could be erected as joint charitable ventures, working not only for spiritual “reward,” but for the betterment of citizens.